Design thinking as a dynamic methodology for information science - Nakano, Natalia [UNESP] (2018)
Purpose - This paper aims to present an overview of the design thinking (DT) methodology applied to information science research focusing on the user journey. DT stages are essential to understand, create and implement solutions based on the identified problems. Design/methodology/approach - The paper applies bibliographic, theoretical and exploratory research based on the literature from DT methodology and information science. Findings - The area of information science has not fully incorporated DT methodology on its practices, and DT presents considerable potential to support user experience. Practical implications - Raise awareness of the information science community regarding the DT methodology as an alternative to apply to various types of research. Originality/value - DT brings a unique contribution to engage people toward innovation in information centers; the paper is original, as it provides insights on the application of DT to improve the user journey related to information.